Evaluation of Accessibility for People with Disability in Public Open Space. (April 2019) - Aini, Q; Marlina, H; Nikmatullah, A
Abstract: Public space should be accessible for all people regardless of certain circles. Accessibility is the availability of pathways for all people, including persons with disabilities and the elderly, measured by safety, convenience, usability and independent. This study evaluates the accessibility for PwDS in public open spaces in Banda Aceh City, Aceh Province, Indonesia. The areas used as the case study are Putroe Phang, Blang Padang and Taman Sari. The research method used is quantitative and qualitative by analyzing the willingness and suitability based on facilities and disability technical guidelines. The convenience of access in public open space measured by factors related to the form, dimensions, colors and textures of an access point. The results showed that Taman Sari has a better facilities and disability technical guidelines than the other two cases. In terms of conformity with the standardization of technical guidelines and convenience of access, Taman Sari is not yet fully functional, especially for persons with disabilities.